Financing of Firms in Developing Countries : Lessons from Research - Ayyagari, Meghana; Demirguc-Kunt, Asli; Maksimovic, Vojislav (World Bank, Washington, DC, 2012)
This paper reviews and synthesizes theoretical and empirical research on the role of finance in developing countries. First, the paper presents the stylized facts about firms in developing nations as well as the legal, financial and broader institutional framework in which these firms operate. Next, the paper focuses on the financing choices available to small and medium firms in developing countries and highlights areas needing additional research.